2012
DOI: 10.1109/tbme.2012.2187650
|View full text |Cite
|
Sign up to set email alerts
|

Speech Understanding Performance of Cochlear Implant Subjects Using Time–Frequency Masking-Based Noise Reduction

Abstract: Cochlear implant (CI) recipients report severe degradation of speech understanding under noisy conditions. Most CI recipients typically can require about 10-25 dB higher signal-to-noise ratio than normal hearing (NH) listeners in order to achieve similar speech understanding performance. In recent years, significant emphasis has been put on binaural algorithms, which not only make use of the head shadow effect, but also have two or more microphone signals at their disposal to generate binaural inputs. Most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Since NCM gives a larger optimal λ at SNR=0 than STOI, it indicates that the algorithm is more sparse or “aggressive” in lower SNR conditions. A previous study (ur Rehman Qazi, van Dijk, Moonen, & Wouters, 2012) showed that CI subjects generally tolerate higher levels of distortion than NH subjects, and therefore, more aggressive noise reduction may be appropriate for CI recipients. To set more varied sparsity levels for CI subjects, NCM was used to initialize the λ values in Experiment III.…”
Section: Methodsmentioning
confidence: 99%
“…Since NCM gives a larger optimal λ at SNR=0 than STOI, it indicates that the algorithm is more sparse or “aggressive” in lower SNR conditions. A previous study (ur Rehman Qazi, van Dijk, Moonen, & Wouters, 2012) showed that CI subjects generally tolerate higher levels of distortion than NH subjects, and therefore, more aggressive noise reduction may be appropriate for CI recipients. To set more varied sparsity levels for CI subjects, NCM was used to initialize the λ values in Experiment III.…”
Section: Methodsmentioning
confidence: 99%
“…For the perceptual evaluation with bilaterally implanted CI users, different parameter settings of the SCNR algorithm were chosen than were used in the instrumental evaluation ( Baumgärtel et al., 2015 ). It has previously been shown ( Qazi, van Dijk, Moonen, & Wouters, 2012 ) that CI users are able to tolerate more signal distortion introduced by noise reduction algorithms compared to NH or HI listeners. Therefore, a more aggressive parameter set was chosen for the bilateral CI evaluation compared to the default setting.…”
Section: Methodsmentioning
confidence: 99%
“…A system using a moderately directional microphone on each ear (Audallion BEAMformer) was shown to provide similar benefit to a unilateral moderately directional microphone (Spriet et al 2007). With two sound processors connected with a bi-directional wireless link, bilaterally implemented directional microphones (B€ uchner et al 2014) or bilateral masking-based technologies (Qazi et al 2012) have shown moderate improvements compared to unilateral adaptive beamforming. However, these systems require two sound processors to be worn, and impact battery life due to the power requirements of the wireless link.…”
Section: Spatial and Dynamic Noise Environment Researchmentioning
confidence: 99%